Wicked theory, naked practice : a Fred Ho reader - Ho, Fred Wei-han (University of Minnesota Press, 2009)
For more than three decades, Fred Ho has been a radical artist and activist. As a composer and saxophonist, he is famed for creating music that fuses Asian and African traditions. The influence of the Black Power and Black Arts movements inspired him to become one of the leading radical Asian American activistartists. Wicked Theory, Naked Practice is a groundbreaking collection of Ho's writings, speeches, and interviews.